Planning of Marketing Extension Program for Citrus in Lattakia Governorate - Syria - Ghanem, Jala Jaber; Yacoub, Ghassan; Baddour, Ghassan (Journal of agricultural, environmental and veterinary sciences, 2022)
This research aimed to identify the knowledge and skill needs of citrus growers in the governorate of Lattakia in the field of citrus marketing, their sources of information, and a proposal for a marketing extension program for citrus fruits based on the results. The data was collected through a questionnaire form. The questionnaire consisted of three parts, the first part included questions to measure farmers’ knowledge of the guiding recommendations related to citrus marketing, the second part included questions to measure farmers’ implementation of those recommendations, and the third part included farmers’ sources of information on citrus marketing. The study sample consisted of 381 citrus farmers in Lattakia Governorate in Syria. It was found that there is a weakness in the farmers’ knowledge (21.5%) and implementation (6.04%) of the extensional recommendations for citrus marketing. The results revealed that farmers relied on their own experience (72.7%), friends and neighbors (55.4%), and the extension system (47%) as sources of their information on citrus marketing. In light of the results, the research recommended the necessity of implementing the proposed marketing extension program, and educating farmers that their implementation of the marketing extension recommendations will improve the marketing reality of citrus.